Aqueous Zinc Batteries with Ultra-Fast Redox Kinetics and High Iodine Utilization Enabled by Iron Single Atom Catalysts - Yang, Xueya; Fan, Huiqing; Hu, Fulong; Chen, Shengmei; Yan, Kang; Ma, Longtao (Nano-Micro Letters, 2023)
Rechargeable aqueous zinc iodine (ZnǀǀI2) batteries have been promising energy storage technologies due to low-cost position and constitutional safety of zinc anode, iodine cathode and aqueous electrolytes. Whereas, on one hand, the low-fraction utilization of electrochemically inert host causes severe shuttle of soluble polyiodides, deficient iodine utilization and sluggish reaction kinetics. On the other hand, the usage of high mass polar electrocatalysts occupies mass and volume of electrode materials and sacrifices device-level energy density. Here, we propose a “confinement-catalysis” host composed of Fe single atom catalyst embedding inside ordered mesoporous carbon host, which can effectively confine and catalytically convert I2/I− couple and polyiodide intermediates. Consequently, the cathode enables the high capacity of 188.2 mAh g−1 at 0.3 A g−1, excellent rate capability with a capacity of 139.6 mAh g−1 delivered at high current density of 15 A g−1 and ultra-long cyclic stability over 50,000 cycles with 80.5% initial capacity retained under high iodine loading of 76.72 wt%. Furthermore, the electrocatalytic host can also accelerate the <span id="MathJax-Element-1-Frame" class="MathJax" style="position: relative;" tabindex="0" role="presentation" data-mathml="<mtext>I</mtext>+↔<mspace width="thinmathspace" /><mtext>I</mtext>2">I+↔I2 conversion. The greatly improved electrochemical performance originates from the modulation of physicochemical confinement and the decrease of energy barrier for reversible I−/I2 and I2/I+ couples, and polyiodide intermediates conversions. Highlights: 1 The porous structure and interconnected conductive pathways accommodate a large amount of iodine, entrap polyiodides and guarantee its efficient utilization. While the Fe single atom catalyst efficiently catalyzes the iodine/polyiodide conversion. 2 With “confinement-catalysis” host, the ZnǀǀI2 battery delivers a high capacity of 188.2 mAh g−1 at 0.3 A g−1, excellent rate capability with a capacity of 139.6 mAh g−1 at 15 A g−1 and ultra-long cyclic stability over 50,000 cycles with 80.5% initial capacity retained under high iodine loading of 76.72 wt%.